Anatomical Study of the Facial Recess with Implications in Round Window Visibility for Cochlear Implantation: Personal Observations and Review of the Literature - Jain,Shraddha (2019)
Abstract Introduction Posterior tympanotomy through facial recess (FR) is the conventional and most preferred approach to facilitate cochlear implantation, especially when the electrode is inserted through the round window. The complications of the FR approach can be minimized by proper understanding of the anatomy of the FR. Objective The present study was undertaken to assess the various parameters of FR and round window visibility, which may be of relevance for cochlear implant surgery. Methods Thirty-five normal wet human cadaveric temporal bones were studied by dissection for anatomy of FR and posterior tympanum. Photographs were taken with an 18megapixels digital camera, which were then imported to a computer to determine various parameters. Results The mean distance from the take-off point/crotch of the chorda tympani nerve (CTN) to the stylomastoid foramen was 4.08 ± 0.8 mm(range of 2.06 - 5.5mm). The variations in the course of the CTN included origin at the level of the lateral semicircular canal. Themean chorda-facial angle in our study was 26.91° ± 1.19°, with a range of 25° to 28.69°. The mean FR length ranged between 9.4 mm and 18.56 mm (mean of 12.41 ± 2.91mm) and varied with the origin of the CTN and pneumatization of temporal bone. The average maximum width of the FR was 2.93 ± 0.4 mm (range 2.24-3.45 mm) and the mean width of the FR at the level of the round window was 2.65 ± 0.41 mm. Conclusion The FR approach provides good access to the round windowmembrane in all cases. In some cases, table adjustment is required.